(untitled) (Journal of Face Aesthetics, 2023)
Interventional facial aesthetic medicine allows the facial skin to maintain a favorable appearance at any age, both in women and men. However, it is important to remember how many factors affect the condition of the facial skin. Some of them are presented in the paper.